SGLT2 Inhibitor Treatment Is Associated With Reduced Cardiac Glucose Metabolism - Brett W. Sperry, MD; Yazan Almohtasib, MD; Ramy Ghaly, MD; Mohammad Abdel Jawad, MD; Andrew J. Sauer, MD; Timothy M. Bateman, MD (JACC: Advances, 2025)
Background: Sodium-glucose cotransporter 2 inhibitors (SGLT2is) have cardioprotective effects without acting directly on the myocardium. Objectives: The purpose of the study was to evaluate the impact of SGLT2i on myocardial glucose utilization. Methods: This retrospective propensity-matched cohort study examined subjects who underwent whole-body 18F-fluorodeoxyglucose (18F-FDG) positron emission tomography for oncologic purposes between 2016 and 2024. A 1:1 propensity match analyzed positron emission tomography-derived myocardial FDG uptake, maximum myocardial standardized uptake value (SUV), and total myocardial glycolysis in SGLT2i-treated vs untreated patients. Results: Among 6,747 subjects, 187 were actively prescribed SGLT2i and matched with 187 who were not. Mean age was 68.4 ± 9.7 years, 57.5% were males, 81.8% had diabetes, and 41.4% had heart failure. Myocardial FDG uptake (to quantify glucose utilization) was absent in 64.7% of patients on SGLT2i and 37.4% not on SGLT2i (P < 0.001), despite higher prescan glucose in those receiving SGLT2i (124 vs 110 mg/dL). SUVmax (5.4 vs 5.8, P = 0.004), volume of myocardial FDG uptake (0.8 cm3 vs 4.6 cm3, P = 0.001), and total myocardial glycolysis (1.6 g vs 20.6 g, P < 0.001) were significantly lower in patients treated with SGLT2i vs those untreated. SGLT2i use blunted insulin-induced increases in total myocardial glycolysis (P-interaction 0.036). There was no difference in background SUVmax and SUVmean in the blood pool and liver. Conclusions: SGLT2i use was associated with a greater suppression of myocardial glucose without affecting background tissue glycolysis despite higher prescan glucose levels. These findings add to the understanding of the effect of SGLT2i on the myocardium and may have implications with respect to cardiac imaging protocols that require glucose manipulation.